BARIOGENESIS DALAM MODEL CERMIN CP - , APRIADI S ADAM ([Yogyakarta] : Universitas Gadjah Mada, 2013)
We have investigated the scenario of baryogenesis in CP Mirror model. This scenario is facilitated by the leptoquark particles, and , with different quantum numbers. Both of these particles can decay into standard model particles and CP Mirror particles. The results of calculations for baryogenesis scenario in the CP Mirror model give Baryon Asymmetry B (10â10â10â6) and lower bound estimate of the mass of the leptoquark mlq & (1015 â 1017) GeV.